Hermeneutika Al-Qur'an Muhammad Arkoun dan Kontribusi Revolusionernya Bagi Pembaruan Studi Aqidah-Filsafat Islam - Safitri, Yuli; Zulkarnaen, Zulkarnaen; Arifinsyah, Arifinsyah (UIN Sumatera Utara, 2025)
Muhammad Arkoun’s Qur’anic hermeneutics offers a critical and transformative framework capable of reopening Islamic religious discourses long confined by orthodox exclusivity. This article examines the epistemological foundations of Arkoun’s hermeneutical project, particularly his concepts of double reading, the distinction between the Qur’anic phenomenon and the closed official corpus, as well as the trilateral structure of the thinkable– unthinkable–unthought. Through these theoretical pillars, Arkoun attempts to deconstruct the established structures of religious authority while formulating possibilities for renewing the study of Islamic theology and philosophy. This study shows that Arkoun’s interdisciplinary approach combining historicism, social anthropology, linguistics, and post-structuralist philosophy provides a revolutionary methodological apparatus for reinterpreting the foundations of Islamic theology. The article argues that Arkoun’s hermeneutics not only critiques the tradition but also offers an epistemological reconstruction for contemporary studies in Islamic creed and philosophy. The findings demonstrate that Arkoun’s intellectual contribution opens new conceptual spaces for reorienting Islamic religious studies from doctrinal-normative frameworks toward critical, reflective, historical, and transformative discourse analysis.